Developing multimedia application model for basic mathematics learning - Pardimin; Apriadi; Ninsiana W.; Ihsan Dacholfany M.; Kamar K.; Kamarul Shukri M.T.; Huda M.; Hananto A.L.; Muslihudin M.; Shankar K.; Kamenez N.V.; Maseleno A. (Institute of Advanced Scientific Research, Inc., 2023)
The challenge on teaching and learning mathematics could be viewed into the number of issues such as traditional method adoption, teachers lack of creativity, and complicated illustration. The need to adopt the strategic and innovative method to help teaching and learning (T&L) on Mathematics in elementary school should be taken into consideration in serious concern. This article attempts to elaborate the application model of basic mathematic learning using multimedia adoption. Through presenting the method on understanding basic mathematics in this case study, descriptive analysis was conducted in ensuring the entire process on the planned stage. The findings revealed that developing model of illustrative mathematic T&L would give insightful value to the entire process in raising the joyful environment to foster the understanding level on absorbing the mathematics learning. This study is expected to contribute the interest stage in learning mathematics in elementary school with making interactive multimedia media. The model of interactive multimedia learning media will be useful to foster student learning interest and make it easier to understand basic mathematics learning materials. 2018, Institute of Advanced Scientific Research, Inc.. All rights reserved.